Social media as sources of information on COVID-19 among students in tertiary institutions in Kenyan - Paul Waititu (ULTIMA Comm, 2021)
The outbreak of COVID-19 in December of 2019 and its relentless spread across the globe has led to an upsurge of information on the pandemic, as scholars, health experts and other authorities rush to publish information meant to enlighten the public on this novel virus. Thanks to social media and its various platforms, most of this information is shared online. However, this rapid spread of information has also given rise to panic and trepidation brought about by generally unverified information on social media. This studysought to assess the student's level of social media use in tertiary institutions, its influence on them, and whether they consider social media a credible source of information on COVID-19. An online questionnaire was administered to a sample of 250 students. Collected data were verified and analysed using SPSS software. The study has found that social media plays a significant role in sharing information on COVID-19 among students in tertiary institutions, with WhatsApps being the most widely used platform. However, despite being greatly influential, many students do not view social media as an accurate or credible source of information on the pandemic. Keywords: COVID-19, Kenya, pandemic, social media, students